One-pot multicomponent synthesis of functionalized 2, 5-disubstituted-1, 3, 4-thiadiazine derivatives. Issue 18 (16th September 2016) - Ramagiri, Raj Kumar; Vaarla, Krishnaiah; Vedula, Rajeswar Rao
ABSTRACT: An atom-efficient and environmentally friendly approach to the synthesis of 2, 5-disubstituted-1, 3, 4-thidiazine derivatives has been developed. These compounds were synthesized by a reaction of 2-(2-bromoacetyl)benzofuran and thiocarbohydrazide with various aryl aldehydes, acetylacetones, and pthalic anhydrides in good yields. The advantages of this methodology are mild reaction conditions, easy workup procedure, clean reaction profile, shorter reaction time, and a wide range of substrate applicability. The structures of all synthesized compounds were confirmed from their analytical and spectral data. GRAPHICAL ABSTRACT: